PI3K/AKT Signal Pathway: A Target of Natural Products in the Prevention and Treatment of Alzheimer’s Disease and Parkinson’s Disease - Long, Hui-Zhi; Cheng, Yan; Zhou, Zi-Wei; Luo, Hong-Yu; Wen, Dan-Dan; Gao, Li-Chen (Frontiers in Pharmacology, 2021)
Alzheimer's disease (AD) and Parkinson's disease (PD) are two typical neurodegenerative diseases increased with age. As the average age of the population increases, so do the health problem and economic burden caused by both diseases. PI3K/AKT signaling pathway regulates signal transduction and biological processes such as cell proliferation, apoptosis and metabolism. And it has been reported to regulate neurotoxicity and mediate neuronal survival through different substrates such as FoxOs, GSK-3, caspase-9 and so on. Accumulating evidences indicate that some natural products can play a neuroprotective role by activating PI3K/AKT pathway, providing an effective resource for the discovery of potential therapeutic drugs. In this review, we summarize the relationship between AKT signaling pathway and AD and PD, and discuss the potential natural products involved in the treatment of both diseases based on PI3K/AKT signal pathway in recent years, so as to provide direction and reference for the further development of Chinese herbal medicine to treat these two diseases.